MEMBANGUN MASYARAKAT SEHAT: PENGUATAN EDUKASI KESEHATAN UNTUK KESEJAHTERAAN BERKELANJUTAN DI MERAUKE - Ricardus, Everistus; Pecamuya, Robertus; Tuakra, Yulianus; Wika, Martinus (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to improve health literacy and awareness in the Merauke community through an interactive community-based education approach. The program begins with mapping health problems in the community, through observation and interviews with community leaders and medical personnel, to identify educational needs related to healthy lifestyles. Based on the identification results, an educational module was developed that integrates local wisdom, as well as materials in the form of infographics, short videos, and audiovisual modules to facilitate community understanding. Health cadre training was carried out to equip local communities to become agents of change who can spread health knowledge in their respective communities. This program also involves simple technology such as social media and WhatsApp groups to expand the reach of health information dissemination, especially in remote areas. Post-intervention evaluation showed that the program was successful in increasing community awareness of the importance of personal hygiene, healthy eating patterns, and mental health management. The community also showed an increase in the implementation of healthy habits, such as washing hands regularly and maintaining environmental cleanliness. Despite challenges in changing healthy eating patterns and limited access to healthy food, the use of technology is effective in supporting the sustainability of the program. This program is expected to have a long-term impact on the quality of life of the Merauke community, by strengthening their capacity to maintain health independently and sustainably.